Odpowiedzi

  • Użytkownik Zadane
2010-01-03T19:08:50+01:00
A) 2x +x-1
dla x= -1
2*(-1) -1-1=-2-1-1=-4
b)
2(-x+4) dla x= -10
2(-10+4)=-20+8=-12
c)
1-y+x dla x=2 , y= -1
1+1+2=4
Najlepsza Odpowiedź!
2010-01-03T19:10:28+01:00
A)
x +x-1 dla x= -1
-1+(-1)-1=-3

b)
2(-x+4) dla x= -10
2(10+4) = 2*14=28

c)
1-y+x dla x=2 , y= -1
1-(-1)+2 = 4
2010-01-03T19:11:46+01:00
2
x² +x-1 dla x= -1
Domyślam się, że taką postać ma to wyrażenie
Musimy w miejsce odpowiednich liter wstawić ich wartość liczbową.

a)x² +x-1 = (-1)² + (-1) - 1 = 1 - 1 - 1 = - 1

b) 2(-x+4) dla x= -10

2(-x+4) = -2x + 8 = -2 * (-10) + 8 = 20 + 8 = 28

c)1-y+x dla x=2 , y= -1

1 - y + x = 1- 2 + (-1) = 1 - 2 - 1 = -2